2014
DOI: 10.1177/0956462413518034
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of HIV-infected patients once diagnosed with acyclovir-resistant herpes simplex virus infection

Abstract: Acyclovir-resistant herpes simplex virus (HSV) infection is common in immunocompromised patients, but the course of such infection is little known. We describe the long-term follow-up of HIV-infected patients diagnosed once with acyclovir-resistant HSV infections. We retrospectively studied all HIV-infected patients between 2000 and 2010 diagnosed with virologically confirmed acyclovir-resistant HSV infection. Patients' socio-demographic and immunovirological characteristics were described. Response to foscarn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
(36 reference statements)
1
9
0
Order By: Relevance
“…The percentage of TK frameshifts observed in our study is clearly above error rates observed in literature suggesting the results are not an artefact (Laehnemann et al, 2016). Those results are in agreement with previous data -obtained by cloning analyses, Sanger method, and other UDS technology -showing that heterogeneous populations (HSV TK-deficient and wild-type HSV mutants) may coexist within clinical isolates in variable proportions (Andrei et al, 2005;Piret and Boivin, 2011;Wang et al, 2007;Van velzen et al, 2012;Fujii et al, 2018;Duan et al, 2009;Seang et al, 2014). ().…”
Section: Discussionsupporting
confidence: 91%
“…The percentage of TK frameshifts observed in our study is clearly above error rates observed in literature suggesting the results are not an artefact (Laehnemann et al, 2016). Those results are in agreement with previous data -obtained by cloning analyses, Sanger method, and other UDS technology -showing that heterogeneous populations (HSV TK-deficient and wild-type HSV mutants) may coexist within clinical isolates in variable proportions (Andrei et al, 2005;Piret and Boivin, 2011;Wang et al, 2007;Van velzen et al, 2012;Fujii et al, 2018;Duan et al, 2009;Seang et al, 2014). ().…”
Section: Discussionsupporting
confidence: 91%
“…Susceptibility test of antiviral drugs for alternative therapies is conducted if there is a positive viral culture. Foscarnet can be given if there is a therapy failure (Seang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We have read with interest the retrospective study: 'Long-term follow up of HIV-infected patients once diagnosed with aciclovir-resistant herpes simplex viruses'. 1 In the study, Seang et al reported some variable healing of aciclovir resistant lesions treated with imiquimod 5% cream. We have also seen a dramatic response to imiquimod treatment in aciclovir-resistant herpes.…”
Section: Dear Editorsmentioning
confidence: 98%